Synthesis, Antimicrobial Activity and Molecular Docking Study of Novel N,2-Diphenylquinazolin-4-amine Derivatives: Synthesis, Docking and Antimicrobial Activities of Some Quinazoline Derivatives - Seydbagian, Nasser; Dehghan-Ghahfarokhi, Esmaeil; Abdollahi, Soosan; Rezaeinasab, Rezvan (Iranian Journal of Pharmaceutical Sciences, 2023)
A new series of derivatives of N, 2-diphenylquinazolin-4-amine (3a-g) was synthesized through nucleophilic substitution. The structures of compounds were characterized by FTIR, 1H-NMR, and 13C-NMR spectroscopy. All synthesized compounds were evaluated for their antimicrobial activities against Gram-positive (Staphylococcus aureus, Bacillus subtilis, Lactobacillus rhamnosus) and Gram-negative (Escherichia coli, Pseudomonas aeruginosa) bacteria and also for antifungal activities, against Candida albicans, using broth microdilution method to determine their minimum inhibitory concentrations (MIC). Most of the compounds have shown moderate to good antibacterial activities, significantly compound 3g at 0.0625 mg/mL concentration had the highest activity against P. aeruginosa. Also, the MIC of compound 3f was 0.0078 mg/mL against S. aureus. Furthermore, the tested compounds exhibited remarkable antifungal activities against C. albicans, significantly compounds 3c and 3g showed the least MIC (equal to 0.0625 mg/mL). Also, a docking study into DNA gyrase has been made for these compounds. The synthesized compounds showed dock score values between -3.05 and -6.13kcal/mol. The highest dock score among them was -6.13 kcal/mol, found for compound 3c.